Aristotle on metaphor - Kurbel, PJ (2019)
Aristotle is the first philosopher in the Western tradition to engage philosophically with the phenomenon of metaphor. Despite his pioneering role I will argue here that his account of metaphor has been widely misrepresented or simply misunderstood. This thesis reconstructs his theory of metaphor against the background of contemporary philosophy of metaphor. I proceed in three steps. Firstly, I develop an interpretation of Aristotle’s remarks about proper and deviant words which lays the foundation for Aristotelian metaphors. In a second step I apply these findings to the account of metaphor he develops in Poetics 21. I argue that Aristotle provides a consistent classification of metaphor against a majority of scholars who think he does not, that his account is not dependent on the notion of substitution, and that he does not defend a semantic theory of metaphor. Finally, in my third chapter I make a fresh start at a theory of metaphor in Aristotle, building primarily on his account of similarity as well as his discussion of ways of seeing a portrait in the Poetics and De memoria. I conclude that Aristotle unites Gricean and noncognitivist strands in his thinking about metaphor, accounting both for the communicative as well as the associative and creative side of metaphor.